Clinical and metabolic characteristics of children with hybrid diabetes mellitus (HD) compared to children with type 2 diabetes mellitus (T2DM): A preliminary comparative study: Hybrid Diabetes in Children - De Sanctis, Vincenzo; Soliman, Ashraf; Alyafei, Fawzia; Alaaraj, Nada; Ahmed, Shayma; Elawwa, Ahmed; Hamed, Noor (Acta Biomedica Atenei Parmensis, 2021)
Background: The term double diabetes or “Hybrid Diabetes (HD)” describes diabetes with combined features of type 1 and type 2 diabetes (T2DM). Patients and Methods: We report the clinical and biochemical characteristics of 7 children with HD and the course of their disease including the response to treatment. The data were compared to 59 children with a diagnosis of T2DM. Variables examined included age, height, weight, body mass index (BMI), triglycerides (Tg), high-density lipoprotein (HDL), and blood pressure. The Weiss criteria were used to diagnose metabolic syndrome (MetS). The atherogenic index of plasma (AIP) was calculated from the standard lipid profile. Four autoantibodies against pancreatic β-cell were measured in all patients. Results: Significant clinical and biochemical differences were detected among children with HD versus T2DM. The mean BMI of children with T2DM was significantly higher than for the HD group. At presentation, the mean C peptide level was significantly lower in HD versus T2DM group and 28% presented with diabetic ketoacidosis (DKA). The percentage of those with full criteria of MetS was significantly higher in T2DM versus HD group as well as the percentage of children with high atherogenic index. After a mean duration of 2.3 months from diagnosis, 4/7 of HD patients stopped insulin therapy and 3 patients had a marked reduction in the insulin requirement. During the follow-up (after 15 ±5 months), 5/7 HD patients required an increase in their insulin dose, one was controlled on a markedly low dose of basal insulin and the last patient did not require any insulin therapy for 40 months. Conclusion: Appropriate assessment of HD is necessary for early and correct diagnosis. Increasing awareness of HD among the general population and primary care practitioners is necessary for successfully and properly treating this complex disease.